Comprehensive Quality Evaluation of Roasted Kernels in Macadamia Nuts Based on Principal Component Analysis and Cluster Analysis - Liyue QIN; Pingping SHI; Ronghui LI; Feifei MA; Xin HU; Daiqin HE; Hui SHEN; Huosheng SU (Shipin gongye ke-ji, 2023)
To explore the quality evaluation indicators of roasted macadamia nut kernels and establish a quality evaluation system, 21 samples of macadamia nuts roasted by different temperature and time duration were selected to determine with 16 quality indicators which included in browning index, moisture, total phenolic content, ABTS+ free radical scavenging activity ratio, acid value, peroxide value, hardness, fracture force, shear force and 7 sensory evaluations. These 16 indicators were comprehensively explored by correlation analysis, principal component analysis and cluster analysis to screen the critical indicators of quality evaluation for roasted kernels in macadamia nuts. As indicated by the research findings, with the augment of roasting temperature and time duration, the indicators including moisture, hardness, fracture force, shear force and sensory evaluation of hardness exhibited downturn trends, but the browning index, acid value, peroxide value, and the sensory evaluation of color, aroma, sweetness, bitterness, crispness, overall preference took on an overall upward trend. Aside from that, the total phenolic content and ABTS+ free radical scavenging activity ratio displayed changing trends of initial augment and subsequent reduction. As demonstrated by the results of correlation analysis on 16 indicators, 11 pairs of indicators had remarkable correlation (P<0.05) and 66 pairs of indicators had extremely noticeable correlation (P<0.01). There was a striking positive correlation between browning index and color, aroma, crispness, bitterness in sensory evaluation and a marked positive correlation between moisture and hardness, fracture force, shear force. What’s more, overall preference was positively associated with browning index, total phenolic content and ABTS+ free radical scavenging ratio, and was negatively linked to hardness, fracture force and shearing force. Furthermore, overall preference was also positively associated with color, aroma, sweetness and crispness in sensory evaluation. The roasted kernels with 130 ℃/30 min obtained the highest comprehensive score in principal component analysis, which indicating the best comprehensive quality in all samples. Meanwhile, by combining with cluster analysis, moisture, browning index, hardness, ABTS+ free radical scavenging activity ratio, acid value and peroxide value were determined as the critical indicators to evaluate the quality of roasted kernels in macadamia nuts. The research findings in this paper would provide a certain theoretical basis and scientific reference for the quality evaluation and processing of roasted kernels in macadamia nuts.